Analisis Literasi Keuangan, Overconfidence dan Toleransi Risiko Terhadap Keputusan Investasi Saham - Hardianto, Hardianto; Lubis, Syarif Hidayah (E-Jurnal Akuntansi; Vol 32 No 3 (2022), 2022)
During the Covid-19 pandemic, the number of stock investors has increased significantly, where the more investment activities there are, the more factors and basis for making investment decisions. The purpose of this study is to analyze the effect of financial literacy, overconfidence and risk tolerance on stock investment decisions in the people of Batam City. The approach used in this research is quantitative method, where data is collected by distributing questionnaires in the form of a Likert scale questionnaire with purposive sampling technique with a sample of 160 respondents. The data analysis method is in the form of multiple linear regression analysis using the SPSS version 25 application. The results show that financial literacy has a positive effect on stock investment decisions, overconfidence has a positive effect on stock investment decisions and risk tolerance has a positive effect on stock investment decisions. Keywords: Financial Literacy; Overconfidence; Risk Tolerance; Investment Decision.